2023
DOI: 10.1111/ene.15998
|View full text |Cite
|
Sign up to set email alerts
|

How to distinguish Guillain‐Barré syndrome from nitrous oxide‐induced neuropathy: A 2‐year, multicentric, retrospective study

Abstract: BackgroundRecreational use of nitrous oxide (N2O) has dramatically increased in recent years, resulting in numerous cases of acute sensorimotor tetraparesis secondary to nitrous oxide‐induced neuropathy (N2On). Challenging clinical features can mimic Guillain‐Barré syndrome (GBS), the main differential diagnosis upon admission. The most sensitive biomarkers for distinguishing between these two conditions remain to be determined.MethodsFifty‐eight N2On patients from three referral centers were retrospectively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…We carefully read the article published in the European Journal of Neurology entitled "How to distinguish Guillain-Barré syndrome from nitrous oxide-induced neuropathy: a 2-year, multicenter, retrospective study" [1]. We aim to propose suggestions regarding the use of vitamin B12 as a biomarker of nitrous oxide (N 2 O) intoxication.…”
Section: What Biological Markers Could Be Used For Diagnosis and Moni...mentioning
confidence: 99%
See 1 more Smart Citation
“…We carefully read the article published in the European Journal of Neurology entitled "How to distinguish Guillain-Barré syndrome from nitrous oxide-induced neuropathy: a 2-year, multicenter, retrospective study" [1]. We aim to propose suggestions regarding the use of vitamin B12 as a biomarker of nitrous oxide (N 2 O) intoxication.…”
Section: What Biological Markers Could Be Used For Diagnosis and Moni...mentioning
confidence: 99%
“…In N 2 O abuse, vitamin B12 is neither specific (prevalence of about 25% in the general population) nor sensitive: only about 50% of N 2 O consumers exhibit vitamin B12 deficiency [1,3].…”
Section: Fortanier Et Al Only Focused On the Significance Of Serum Vi...mentioning
confidence: 99%
“…At first evaluation, median lower limb Medical Research Council (MRC) sum score was 26 (normal: 30), median Romberg score was 2 (meaning significant imbalance without falls on Romberg maneuver; from 0 normal to 3 fall), median modified INCAT Sensory Sumscore was 3.5 (normal: 0, maximum score: 16). Another recent study found that in patients with N 2 O-induced neuropathy, at least half of the MRC sum score reduction was due to anterior tibialis weakness in 60.4% of patients [ 10 ]. Additionally, in a Taiwanese study from 2019, authors compared N 2 O abusers and vitamin B12 deficiency patients, and found that the former had more severe motor deficit quantified by the MRC and the Neuropathy impairment Score, predominantly in the lower limbs [ 11 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Many of these patients were treated inappropriately with intravenous immunoglobulins [ 23 ]. To avoid unnecessary treatment, some authors investigated clinical or electrophysiological clues, and established a list of elements to differentiate the two conditions ( Table 1 ) [ 10 , 24 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation